The Influence of Workload, Work Environment and Technological Usage on Employee Performance at the Tangerang Regency Fisheries Service Office - Mia Damayanti; Dudung Hadiwijaya; Priyo Susilo (Green Publisher Indonesia, 2024)
Urgency in this study is based on the results of the interim observations in the respondents of the research, namely, the staff of the Tangerang Regency Fisheries Service Office, there are some problems related to the Work Load, Work Environment, and Technological Usage that can be an impediment to achieving the performance of the officials. This research is carried out because there are still inconsistent results from previous researches. The author performs re-research with different Research Objects as well as different survey respondents are expected to produce appropriate results. The total of respondents in this study was 75 respondents. Technical analysis of double linear regression is used as data analysis and analyzed using the SPSS Version 24 application. This study used quantitative methods. This research aims to find out the impact of the workload, work environment and technological usage on employee performance of the Tangerang Regency Fisheries Service Office. The targeted output is that the Tangerang Regency Fisheries Service Office can perform well. The results of the study showed that the workload has a negative and significant impact on employee performance, the work environment has a positive and significant impact on the employee performance, Technological usage with a positive and significant effect on employee performance and workload, the work environment and technological usage combined have a significant impact on employee performance. The massive impact of workload, work environment and technological usage on employee performance is 64.60% while the remaining 35.40% is influenced by other factors not studied in this study.